A temporal logic approach to supervisory control of discrete-event systems - Seow, Kiam Tian. (2009)
This thesis addresses the problem of existence and synthesis of supervisory conirol for a class of logical discrete-event systems (DESs). The existence problem arises under a control-theoretic scenario, the most basic of which is the set of events in a DES being a disjoint union of controllable and uncontrollable events. The existence of supervision becomes an issue because oidy controllable events can be prevented from occurring; those pre-defined as uncontrollable can never be. Thus, a supervisor, whose purpose is to ensure that a DES under its control satisfies some logical behavioral constraint known simply as a control objective, may not exist relative to the given control objective. Based on the temporal logic canonical framework, the thesis develops basic results of control-theoretic analysis and synthesis across three canonical classes of control objectives, viz., safety, response and reactivity.